FRI0713 Low bone mineral density is the main contributor to falls-related health burden in the european elderly. (15th June 2017) - Sanchez-Riera, L; Wilson, N; Prieto-Alhambra, D; Cooper, C; Dreinhöfer, K; Woolf, A; March, L; Halbout, P
Abstract : Background: Falls are the leading injury type in elderly populations and a major health burden and cause of death globally. Most of such burden is due to bone fractures. In the Global Burden of Diseases (GBD) Initiative, the attributable burden of falls due to low bone mineral density (BMD) was analysed through its relationship with fractures. Objectives: To measure the percentage of disability-adjusted life years (DALYs), years lived with disability (YLDs) and deaths due to falls attributable to low BMD in European population for the year 2015. Methods: The estimates followed the Counterfactual Risk Assessment Methodology used in the GBD study (1). Systematic review was performed seeking population-based studies with femoral neck (FNBMD) measured by Dual-X-Ray-Absorptiometry in people 50 years and over. Age- and sex- specific levels of mean +/-SD FNBMD (g/cm 2 ) were extracted from eligible studies, and this was used as the exposure variable. The age and sex-specific 99th percentile from non-Hispanic whites in the National Health and Nutrition Examination Survey (NHANES) 2009–2010 was used as theoretical minimum risk factor exposure distribution, to estimate the potential impact fraction (PIF) of FNBMD for fractures. Relative risks of FNBMD for fractures were obtained from a previous meta-analysis (2). Coded hospital data was used to calculate the fraction of falls-related deaths due to fractures. Disability levels were established by applying disability weights to each type of fracture. Then, PIFs were applied to obtain attributable deaths and disability due to low BMD. Results: The percentage of falls-related preventable deaths attributable to low BMD is around 9% in the 50–54 age group, increasing to 84% in those aged 80 years and over. Total health burden (DALYs) and disability attribution (YLDs) also increase with age, from 19% and 25% in 50–54 years old, respectively, to 61% and 44% and population aged 80 years and above, respectively. Low BMD constitutes the most important preventable risk factors for falls-related DALYs from 50 years and above, followed by alcohol, occupational risk and smoking. Conclusions: Low BMD is a major preventable risk factor that explains a very remarkable proportion of falls health burden in Europe, in particular in those aged 70 years and above. This is a growing concern, given the population trajectories, and requires urgent attention. References: Forouzanfar M et al, Lancet 2016., Johnell O et al, JBMR 2015. Disclosure of Interest: None declared